2001
DOI: 10.1080/15017410109510766
|View full text |Cite
|
Sign up to set email alerts
|

Relationships with parents and friends, self‐esteem and depression among adolescents with visual impairments

Abstract: Social relationships with parents and friends, depression, and the mediating role of self-esteem between relationships and depression were studied among 115 adolescents with visual impairments attending regular Finnish schools. The control group consisted of normally sighted classmates of visually impaired adolescents (N=607). The data were collected using a self-report questionnaire.The results showed no significant difference in the prevalence of depression between visually impaired adolescents and the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
3
11
1
Order By: Relevance
“…First, mental health status in female visually impaired athletes was worse than that of men in the current study. Consistent with our findings, several past reports showed the gender difference of the mental health status in visually impaired students; girls had more serious depressive and anxiety symptoms than boys [36-39]. Our findings also agree with the majority of the literature on non-visually impaired athletes, which has found that female athletes show higher scores of anxiety and depression than male athletes [40-42].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, mental health status in female visually impaired athletes was worse than that of men in the current study. Consistent with our findings, several past reports showed the gender difference of the mental health status in visually impaired students; girls had more serious depressive and anxiety symptoms than boys [36-39]. Our findings also agree with the majority of the literature on non-visually impaired athletes, which has found that female athletes show higher scores of anxiety and depression than male athletes [40-42].…”
Section: Discussionsupporting
confidence: 93%
“…This finding is not consistent with previous studies showing better social support, especially support from friends, is vital to help children with visual impairments in reducing the number and severity of their emotional problems [37, 46, 47], as well as their depression and anxiety symptoms [38, 48]. Of note, young people with visual impairments have fewer chances to make friends, face problems of social isolation and, consequently, they develop emotional and communication problems [36]. Different types of mental health problems may depend on lifestyle, support from family and friends, level of integrations, and social networks [49].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The period of adolescence can cause a great deal of anxiety for the visually impaired person, who faces not only the usual developmental challenges but also the added strain of his or her physical handicap (Huurre et al 2001). Many studies have shown the increased vulnerability and difficulties occurring during the growth and development of children and adolescents with VI (Kef & Dekovic 2004, Robinson & Lieberman 2004, Shapiro et al 2008.…”
Section: Hopelessnessmentioning
confidence: 99%
“…The period of adolescence can cause a great deal of anxiety for the visually impaired person, who faces not only the usual developmental challenges but also the added strain of his or her physical handicap (Huurre et al . 2001).…”
Section: Introductionmentioning
confidence: 99%